2017
DOI: 10.1007/s13770-017-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biocompatibility Characterizations of in Situ Chondroitin Sulfate–Gelatin Hydrogel for Tissue Engineering

Abstract: Novel hydrogel composed of both chondroitin sulfate (CS) and gelatin was developed for better cellular interaction through two step double crosslinking of N-(3-diethylpropyl)-N-ethylcarbodiimide hydrochloride (EDC) chemistries and then click chemistry. EDC chemistry was proceeded during grafting of amino acid dihydrazide (ADH) to carboxylic groups in CS and gelatin network in separate reactions, thus obtaining CS-ADH and gelatin-ADH, respectively. CS-acrylate and gelatin-TCEP was obtained through a second EDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
0
18
0
3
Order By: Relevance
“…Bang et al reported chondroitin sulphate-based dual cross-linked hydrogels with gelatin grafting for improving the cell-adhesive properties of the chondroitin sulphate. They used the Michael type click chemistry reaction method and N-(3-diethylpropyl)-Nethylcarbodiimide hydrochloride chemistry for the gel formation and the hydrogels were tested for its application related to tissue engineering and drug delivery [100]. These different works related to thiol-based click chemistry reactions show potentials of this method in developing novel hydrogel biomaterials for tissue engineering applications.…”
Section: Thiol Group-based (Thiol-michael) Pseudo-click Hydrogels Formentioning
confidence: 99%
“…Bang et al reported chondroitin sulphate-based dual cross-linked hydrogels with gelatin grafting for improving the cell-adhesive properties of the chondroitin sulphate. They used the Michael type click chemistry reaction method and N-(3-diethylpropyl)-Nethylcarbodiimide hydrochloride chemistry for the gel formation and the hydrogels were tested for its application related to tissue engineering and drug delivery [100]. These different works related to thiol-based click chemistry reactions show potentials of this method in developing novel hydrogel biomaterials for tissue engineering applications.…”
Section: Thiol Group-based (Thiol-michael) Pseudo-click Hydrogels Formentioning
confidence: 99%
“…Hydrogels with similar G ′ that were formed by different crosslinking formulations were evaluated in cytotoxicity assays to understand changes in cytotoxicity due to differences in Ru and APS concentrations. The cytotoxicity assay tests the utility of Ru-mediated dityrosine crosslinked hydrogels in applications for which buffer exchange of the hydrogel is difficult, such as in-situ hydrogel applications (Bang et al, 2018) where crosslinking reagents necessarily come into direct contact with cells. This study demonstrates a systematic approach to prepare non-cytotoxic biomaterials with targeted elastic moduli given any appropriate tyrosyl-containing polymer by controlling the concentrations of Ru and APS used during photocrosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…The grafting of ADH to chondroitin sulfate (CS) and gelatin resulted in CS-ADH and gelatin-ADH, respectively. After the subsequent reaction mediated by EDC, the in situ gelatin-CS hydrogel was obtained, which showed excellent biocompatibility, especially the application potential in cartilage tissue engineering [75].…”
Section: Gelatinmentioning
confidence: 99%